Shear failure criterion for RC T-beams. (1st April 2018) - Kotsovou, Gregoria M.; Cotsovos, Demitrios M.
Highlights: A new failure criterion is proposed for accurately predicting the shear capacity of RC T-beams. The development of the criterion is based on assumptions different from those adopted by the design codes. These assumption relate to the mechanics underlying RC structural response at the ultimate limit state. A database is formed from test data describing the effect of key design parameters on the load-carrying capacity of T-beams. The predictions of the proposed criterion are compared to those of the existing codes and test data. The proposed criterion often provides predictions closer to the test data compared to the codes. Abstract: The paper is concerned with the development of a failure criterion capable of accurately predicting the shear capacity of reinforced concrete T-beams while correctly accounting for the beneficial effect of the increase of the compressive zone due to the presence of flanges. The development of the subject criterion is based on an alternative design method (the compressive force path method) that leads to predictions of reinforced concrete structural behaviour and design solutions considerably different compared to those of the current design codes without however compromising structural performance requirements (mainly associated with ductility and strength). The validity of the proposed failure criterion is verified through a comparative study of the calculated values with their experimentally-established counterparts obtained from an extensive literature survey. Through this comparative study it is demonstrated that the predictions of the proposed criterion provide a closer fit to the available experimental data than their counterparts obtained from the design codes considered.